2017
DOI: 10.1038/bjc.2017.72
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ovarian cancer screening on sexual activity and functioning: results from the UK collaborative trial of ovarian cancer screening RCT

Abstract: Background:To examine the impact of multimodal (MMS) and ultrasound (USS) screening on the sexual activity and functioning of 22 966 women in the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) RCT.Methods:Fallowfield's Sexual Activity Questionnaire (FSAQ) was completed prior to randomisation, then annually in a random sample (RS) of women from MMS, USS and control groups. Any women in the study who required repeat screening due to unsatisfactory results formed an Events Sample (ES); they complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Screening did not appear to raise anxiety but higher psychological morbidity (worry) and lower pleasure scores were reported by those who had to undergo Level 2 (transvaginal ultrasound with or without CA125) screening due to abnormal results on the annual screen. [123][124][125] At a median follow-up of 11.1 years, compared to the control arm, the trial demonstrated a significant (p=0.0001) stage shift in invasive epithelial ovarian, tubal and peritoneal cancers with multimodal screening (36.1% Stage I or II) compared with control (23.9%) but not with ultrasound screening (22.4%; p=0.604). 122 There was a trend to reduction in mortality which was not statistically significant in either screen arm (Figure 1).…”
Section: General Populationmentioning
confidence: 97%
“…Screening did not appear to raise anxiety but higher psychological morbidity (worry) and lower pleasure scores were reported by those who had to undergo Level 2 (transvaginal ultrasound with or without CA125) screening due to abnormal results on the annual screen. [123][124][125] At a median follow-up of 11.1 years, compared to the control arm, the trial demonstrated a significant (p=0.0001) stage shift in invasive epithelial ovarian, tubal and peritoneal cancers with multimodal screening (36.1% Stage I or II) compared with control (23.9%) but not with ultrasound screening (22.4%; p=0.604). 122 There was a trend to reduction in mortality which was not statistically significant in either screen arm (Figure 1).…”
Section: General Populationmentioning
confidence: 97%
“…Screening for disease in the general population did not increase anxiety (91) or result in a reduction in sexual activity or functioning (92). However, an abnormal screening result and need for second line tests did result in increased psychological morbidity, primarily due to worry (91), as well as decreased sexual pleasure in the short term (92).…”
Section: Morbidity (Physical and Psychological)mentioning
confidence: 99%
“…16 Secondary objectives include measuring the effects of screening on anxiety levels, psychological morbidity, and sexual activity, and have been published previously. 17-19…”
mentioning
confidence: 99%
“…These findings were, however, not associated with ovarian screening, except for women with abnormal results who underwent repeated or higher level screening. 19…”
mentioning
confidence: 99%